Fibrinolytic markers and vasodilatory capacity following acute exercise among men of differing training status - Baynard, T.; Jacobs, H. M.; Kessler, C. M.; Kanaley, J. A.; Fernhall, B. (European Journal of Applied Physiology, 2007)
We evaluated the effect of differing physical activity patterns on fibrinolysis and vasodilatory capacity using a cross-sectional design with 16 endurance-trained (ET) (mean ± SE) (28 ± 6 years), 14 resistance-trained (RT) (28 ± 7 years), and 10 untrained (UT) (26 ± 7 years) men. t-PA and PAI-1 activity and t-PA antigen were measured before and after a maximal treadmill test (VO2peak). Vasodilatory capacity was assessed using strain-gauge plethysmography on the forearm following reactive hyperemia (RH) before and after the treadmill test. The ET group had a smaller body mass index (BMI) (22.8 ± 0.5 ET, 26.4 ± 0.4 RT, 25.1 ± 0.8 UT kg m-2) (P < 0.05) and a greater VO2peak (57 ± 1 ET, 42 ± 2 RT, 45 ± 2 UT mL min-1 kg-1) (P < 0.05). Peak vasodilatory capacity (29.7 ± 2 ET, 32.0 ± 2 RT, 27.4 ± 2 UT mL min-1 100 mL of tissue) was similar between groups before and after exercise. Area under the curve for forearm blood flow was greater following acute exercise (212 vs. 122, P < 0.05), again with no differences between groups. t-PA activity and antigen increased following maximal exercise in all groups (P < 0.0001), with no group differences. PAI-1 activity decreased the least in RT after exercise (70% decrease vs. 86% ET and 82% UT; P < 0.05). The change in t-PA activity with exercise was not related to exercise-induced change in overall vasodilatory capacity. These findings demonstrate that in healthy young men different physical activity patterns do not appear to impact the exercise-induced changes in fibrinolysis or vasodilatory capacity.